Program Edukasi Memerah ASI terhadap Pengetahuan Ibu Nifas dalam Memerah ASI - Mulyaningsih, Nanik; Wahyuni, Sri; Yulaikah, Siti (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Exclusive breastfeeding in Indonesia has not yet reached 100%. One effective strategy to support successful breastfeeding is by educating mothers on how to express breast milk. Educating mothers on this practice is crucial to enhancing their knowledge and supporting the success of exclusive breastfeeding. This activity aims to implement a breast milk expression education programme for postpartum mothers at the Gantiwarno Community Health Centre and to monitor changes in knowledge through pre- and post-session. Methods: This community service was conducted in the working area of the Gantiwarno Community Health Centre, Klaten, in October 2022, targeting 23 postpartum mothers who were selected purposively. The intervention took the form of approximately 20 minutes of education on expressing breast milk using leaflets, preceded by a pre-test and followed by a post-test immediately after the session. Knowledge was measured using a structured questionnaire, and changes in pairs were analysed using the Wilcoxon test (α=0.05) after obtaining consent to participate. Results: The majority of participants were aged 20–35 years (73.9%), had a high school education (69.6%), were not formally employed (65.2%), and were multiparous (69.6%). Before the session, knowledge was predominantly in the ‘fair’ category (60.9%); after education, the ‘good’ category increased to 39.1%. Paired analysis showed a significant increase (p=0.03). Conclusion: Education on expressing breast milk positively affected the knowledge of postpartum mothers at the Gantiwarno Health Center. Therefore, it is important to provide such education to improve maternal knowledge, which can contribute to achieving the goal of exclusive breastfeeding.